Investigation of the hydraulic characteristics for portable rubbish & sediment trap - Abd. Rahman, Norhan; Abu Hassan, Shukur (Faculty of Civil Engineering, 2008)
Rubbish trap is devises used to prevent large items polluting waterways. They are used in stormwater drains, urban wetlands, river and other locations. They generally collected larger items from the water, such as take away containers, leaves, bottles and plastic bags. The purpose of this research is to determine the efficiency of rubbish trap in terms of the trapping rubbish and water quality improvement as well as to evaluate the efficiency of perforated wall’s rubbish traps and to compared with existing mesh type in terms of trapping litter or rubbish. A laboratory test are also conducted to study the rubbish traps characteristic in four difference types of scale rubbish modelling in various discharge and quantity of artificial rubbish collected. Data taken from laboratory test are energy loss and backwater flow. The study is based on rubbish trap at L52 and trash screen at L50 which is located at UTM campus and rubbish trap at Taman Universiti, Skudai. From the results obtained, rubbish trap at L52, L50 and Taman Universiti shows the effectiveness to trap rubbish and sediment where it can reduce the amount of suspended solids in water. However, the existing rubbish trap (mesh type) is more effective than new rubbish trap (perforated).